PELATIHAN PEMBUATAN PUPUK ORGANIK SEBAGAI PENDUKUNG PERTANIAN ORGANIK KELOMPOK TANI HIDUP BARU - Bayu Mahendra; Ernantje Hendrik; Selfius P. N. Nainiti; Maximilian M. J. Kapa; Paulus Un (Jurnal Pengabdian Masyarakat Berkelanjutan, 2025)
Farmer groups have an important role in the development of the agricultural sector. The production of organic vegetables not only supports environmental sustainability, but also increases the added value of agricultural products. However, in its implementation, Farmer Groups often face various obstacles, one of which is the limited availability of organic fertilizers. Organic fertilizers can support plant production and can replace the role of chemical fertilizers. Another problem faced by Farmer Groups, especially the New Living Farmers Group, is the increasing difficulty of obtaining chemical fertilizers. In addition to the increasingly expensive price of chemical fertilizers, the circulation of fake fertilizers in the market is also a challenge for farmers. This condition encourages the need for a more sustainable solution in meeting the fertilizer needs of Farmer Groups, namely by producing their own organic fertilizers independently.